OC-077 The short term outcomes from 2468 bariatric procedures: a single centre of excellence. (22nd June 2015) - Riaz, AA; Ferguson, J; Talbot, M
Abstract : Introduction: Bariatric surgery is associated with long-term weight loss and decreased overall mortality. 1 The development of the 'Centre of Excellence' model has seen improvements in bariatric outcomes. 2 We wish to publish the short-term results from a single Centre of Excellence in Australia. Method: A database of 2468 patients was retrospectively created between 2010 and 2013. All patients underwent laparoscopic sleeve gastrectomy (LSG) (n = 1642), laparoscopic gastric band (LGB) (n = 554) and laparoscopic gastric bypass (LRYGB) (n = 272). The primary endpoint was overall mortality. The secondary endpoints were leak rate, length of hospital stay, readmission rates and complication rates. Results: There were no deaths. There were a total of 9 leaks (LSG-5; LGB-4; 0.36%). The median lengths of stay for LSG, LGB and LRYGB were 3 days, 3 days and 1 day respectively. There were a total of 77 unplanned readmissions for 64 patients (readmission rate 3.1%). 31 readmissions (40.3%) were for dehydration and 14 (18.2%) were for benign abdominal pain. Twenty-four patients were taken back to theatre for complications on 30 occasions (0.97%; LSG-11, LRYGB-9, LGB-4). Ten (33.3%) take back procedures were in revision cases (LSG-1; LRYGB-7; LGB-2). Conclusion: Bariatric surgery can be performed safely with a satisfactory short term morbidity profile in high-volume centres. Disclosure of interest: None Declared. References: Sjöström L, Narbro K, Sjöström CD, et al . Effects of bariatric surgery on mortality in Swedish obese subjects. N Engl J Med. 2007;357(8):741–52 Gebhart A, Young M, Phelan M, Nguyen NT. Impact of accreditation in bariatric surgery. Surg Obes Relat Dis. 2014;10:767–773